2013
DOI: 10.1890/11-1454.1
|View full text |Cite
|
Sign up to set email alerts
|

Postfire changes in forest carbon storage over a 300‐year chronosequence ofPinus contorta‐dominated forests

Abstract: A warming climate may increase the frequency and severity of stand-replacing wildfires, reducing carbon (C) storage in forest ecosystems. Understanding the variability of postfire C cycling on heterogeneous landscapes is critical for predicting changes in C storage with more frequent disturbance. We measured C pools and fluxes for 77 lodgepole pine (Pinus contorta Dougl. ex Loud var. latifolia Engelm.) stands in and around Yellowstone National Park (YNP) along a 300-year chronosequence to examine how quickly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 109 publications
(205 reference statements)
11
116
2
Order By: Relevance
“…In the case of stand-replacing wildfires this requires information spanning at least several centuries, and at Chickaree Lake this required several millennia, well beyond the length of both observational and tree-ring records. Many studies have reported ecosystem impacts or recovery times from individual fire events and then extrapolated to infer scenarios that would lead to C gain or loss (Dunnette et al, 2014;Kashian et al, 2013;Mack et al, 2011;Smithwick et al, 2009). In contrast, our paleo-informed scenario highlights the importance of variability in fire timing and severity over multiple fire events for carbon cycling dynamics, independent of complete shifts in a fire regime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of stand-replacing wildfires this requires information spanning at least several centuries, and at Chickaree Lake this required several millennia, well beyond the length of both observational and tree-ring records. Many studies have reported ecosystem impacts or recovery times from individual fire events and then extrapolated to infer scenarios that would lead to C gain or loss (Dunnette et al, 2014;Kashian et al, 2013;Mack et al, 2011;Smithwick et al, 2009). In contrast, our paleo-informed scenario highlights the importance of variability in fire timing and severity over multiple fire events for carbon cycling dynamics, independent of complete shifts in a fire regime.…”
Section: Discussionmentioning
confidence: 99%
“…DayCent submodels associated with tree physiological parameters, site characteristics, soil parameters, and disturbance events were modified using available site-specific observations (Dunnette et al, 2014;Sibold et al, 2007), values from the literature (Kashian et al, 2013;Turner et al, 2004), and publically available climate and soil databases. Climate data required for DayCent include daily minimum and maximum temperature and precipitation, which were obtained for a 30-year period from DAYMET (Thornton, 2012).…”
Section: Model Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the mean annual growth response, both residual overstory and understory trees species showed variable growth responses [42,55,67] and in some instances reached up to 400% from the pre-MPB conditions [67]. Generally, MPB attacks older trees (>60 years of age) and if we consider the growth pattern of pine trees, it reveals that peak productivity can be achieved 24-60 years after stand development and declines thereafter to 16%-48% of maximum values by the age of 200-350 years [68][69][70]. Therefore, disturbance caused by MPB "resets" the pine development to an earlier and possibly more productive stage and killed pine volume can be offset by the increased growth [42,55,67,68].…”
Section: Growth Response Of Residual Live Treesmentioning
confidence: 99%
“…Models suggest this biome will experience rapid temperature increases during the 21st century, with a potential 30-500% increase in burn rates (6)(7)(8)(9). Both fire size and the frequency of large fire years are expected to increase (8,10,11), with a cascading effect on ecosystem dynamics (12)(13)(14)(15)(16) and carbon storage (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%